Legal information system as a source of knowledge about law. The concept of the architecture of an expert legal information system - Chomiak-Orsa, Iwona; Greńczuk, Andrzej (System informacji prawnej jako źródło wiedzy o prawie. Koncepcja architektury ekspertowego systemu informacji prawnej, 2020)
This article aims to present the concept of the architecture of an expert legal information system. The authors of this article, working with entrepreneurs in the field of supporting business activities, identified a significant gap in ICT solutions providing legal knowledge. The research question that inspired the considerations contained in the article is: Do the current solutions supporting the provision of legal knowledge enable the creation of an expert legal information system? In order to answer this question the authors conducted a critical analysis of the literature and identified ICT solutions used by entrepreneurs in the field of obtaining and processing legal information. The article presents the main sources of legal information, trends in the development of ICT solutions and the areas of their application. The key part of the article is the concept of an expert legal information system architecture
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 3 (57), s. 22-33
Keywords: legal information system; law; legal informatics; legal normssystem informacji prawnej; prawo; informatyka prawnicza; normy prawne